Simulating The Use of UAV Photogrammetry For Monitoring Land Subsidence at Urban Area - Dimas C Alamsyah (Syntax Literate, 2022)
The Unmanned Aerial Vehicle (UAV) photogrammetry method has been widely used in various applications. One of the potential photogrammetry methods is to estimate the land deformation, e.g., land subsidence. This study aims to analyze the opportunity of UAV photogrammetry utilization for detecting the land subsidence urban areas, including relatively low cost and wide area coverage in a relatively short time. Two photogrammetry measurements were conducted in two different epochs with different flight altitudes to analyze the potential use of the photogrammetry method. The Digital Surface Model (DSM) generated from two different observation periods will be compared to obtain a land subsidence model. Based on the result, the photogrammetry method can detect land subsidence if a minimum subsidence value of 5 cm exists for an altitude flight height of 80 meters, 10 cm for an altitude flight height of 100 meters, and 11 cm for an altitude flight height of 150 meters. We also highlight several things to consider when applying the photogrammetry method to observe land subsidence, e.g., remove the uncorrelated height values obtained from different observations.